The care to the parturient provided by obstetric nurses in the Midifery Project: an experience report (Revista Latino-Americana de Enfermagem, 2002)
This study focuses on the nursing care models that value the woman in childbirth process. Authors described the humanized care provided to the parturient by obstetric nurses in the "Midwifery Project" developed at a University Maternity Hospital. They emphasized that the practice of these models enable the nurse's active participation in the childbirth process, resulting in the satisfaction of the parturient and of the professional.